(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Diabetes mellitus affects over 537 million people globally, with projections reaching 700 million by 2045. Insulin administration is a critical component of diabetes management, particularly for type 1 diabetes patients and a significant portion of those with type 2 diabetes. Despite its clinical importance, gaps remain in nursing students’ knowledge and psychomotor skills related to insulin administration. Simulation-based learning has emerged as a transformative pedagogical strategy to bridge these gaps and enhance general self-efficacy in nursing students. Objective: This scoping review aimed to explore and summarize existing literature on the impact of simulation-based learning on general self-efficacy in insulin administration among novice nursing students. Methods: A comprehensive literature search was conducted using ProQuest, Ovid, Scopus, and PubMed databases. Studies published between January 2018 and November 2024 were included. Relevant descriptors such as “Simulation Based Learning” OR “insulin administration” AND “General Self-efficacy” were used. A total of 16articles were included based on eligibility criteria. Data was extracted and synthesized using the PRISMA framework. Results: This scoping review included 16 relevant studies, with most demonstrating that simulation-based learning significantly improves nursing students’ general self-efficacy, clinical competence, and confidence in managing technical tasks. Simulation techniques such as virtual reality, standardized patient encounters, and low-cost simulators were effective in enhancing psychomotor and communication skills essential for insulin administration. However, only a limited number of studies directly addressed insulin administration training in nursing students, highlighting a critical gap. Most research focused broadly on clinical skills or patient populations, indicating a need for more targeted simulation-based training specific to insulin delivery. Conclusion: Simulation-based learning is a promising educational strategy for enhancing self-efficacy and technical competence among nursing students. Despite limited direct evidence on insulin administration training, the broader literature supports simulation’s role in preparing students for real-world clinical challenges. Integrating insulin-specific simulation scenarios into early nursing curricula could bridge knowledge-practice gaps, foster confidence, and ensure safer patient care in diabetes management